A dimensão político-pedagógica da “comunicação sem equívocos” frente aos desafios da escola para todos: novos lugares interpretativos para a prática docente - Tfouni, Leda Verdiani; Martha-Toneto, Diana Junkes Bueno [UNESP]; Adorni, Alessandra (My University, 2011)
The aim of this paper is to present some considerations on discursive positions that challenge the textual production of a student from Cycle II Elementary School. We intend to show how a biased reading of the student’s text might not observe significant textual features and disregard the student’s level of literacy, thus ignoring the insertion of this writing in a socio-historical context. Such an approach, while defined by ideology, is determined by the pedagogical discourse that focuses on formal patterns of language, which prevents the teacher from identifying rich and interesting linguistic and textual procedures in the text in question, indicative of the student's literacy and his/her potential for authorship. This reading mostly denies the efforts that have been made to reverse the exclusion of public schools students, weakening the idealist discourse that claims for a “school for everybody”.

O objetivo do presente artigo é tecer algumas considerações sobre a produção textual de um aluno do Ciclo II do Ensino Fundamental. Pretende-se mostrar como o texto do aluno pode ser lido por um viés que deixa de observar características textuais importantes, desconsiderando o seu nível de letramento e, portanto, desconsiderando a inserção dessa escrita em um contexto sócio-histórico. Tal viés, ao mesmo tempo em que é definido pela ideologia, é determinado por um equívoco interpretativo embasado pelo discurso pedagógico escolar que privilegia a língua culta, o que impede o leitor de identificar, no texto em questão, procedimentos linguístico-textuais interessantes e ricos, indicativos do letramento do aluno e de seu potencial de autoria. Essa leitura denega, em grande parte, os esforços que têm sido feitos para reverter a exclusão dos alunos da escola pública, enfraquecendo o discurso idealista que defende a existência de uma escola para todos.
The political-pedagogic dimension of unmistaken communication facing the challenges of a “ School for Everybody”: new interpretative places to the teaching practice
Keywords: Letramento; escrita no Ensino Fundamental; Análise do Discurso; Literacy; writing in basic education; discourse analysis